Analysis of haemostasis biomarkers in patients with advanced stage lung cancer during hypofractionated radiotherapy treatment. Issue 5 (May 2018) - Wolny-Rokicka, Edyta; Brzeźniakiewicz-Janus, Katarzyna; Wydmański, Jerzy; Tukiendorf, Andrzej; Zembroń-Łacny, Agnieszka
Objective: To investigate the relationship between changes in inflammatory and coagulatory biomarkers before and after short palliative radiotherapy in patients with advanced stage lung cancer. Methods: This prospective observational single-centre study enrolled patients with histologically- or cytologically-confirmed lung cancer who were eligible for palliative radiotherapy. Inflammatory and coagulatory biomarkers including complete blood count, D-dimer and fibrinogen levels were evaluated before and after short hypofractionated radiotherapy. Results: Seventy-two patients with advanced stage lung carcinoma were enrolled in this study. Metastases were associated with an increase in white blood cells, neutrophils and mean platelet volume. Increased volume of the primary tumour had a borderline level of correlation with white blood cell and neutrophil counts. After radiotherapy, white blood cells, neutrophils, haemoglobin and lymphocyte counts were decreased. After radiotherapy, the change in fibrinogen and mean platelet volume were borderline significant. Conclusion: The levels of inflammatory and coagulatory biomarkers can be used to monitor treatment.